ANALISIS KESESUAIAN PELAYANAN FARMASI KLINIK BERDASARKAN PERMENKES NO. 73 TAHUN 2016 DI APOTEK KABUPATEN JEPARA - Nova Oktaviana; Ria Etikasari; Ahmad Suriyadi Muslim (Yayasan Nusantara Hasana Berdikari, 2026)
Clinical pharmacy services in pharmacies play a very important role in ensuring the safe, rational, and effective use of medicines. The provisions regarding clinical pharmacy services are regulated in the Ministry of Health Regulation No. 73 of 2016 concerning Standards of Pharmacy Services in Pharmacies. This study aims to analyze the compliance of pharmacies in Jepara Regency with the implementation of clinical services based on the Ministry of Health Regulation No. 73 of 2016 and to assess the extent to which the seven aspects of clinical pharmacy services—prescription assessment and services, dispensing, drug information services, patient counseling, home pharmacy care, drug therapy monitoring, and adverse drug reaction monitoring—have been carried out according to the standard. The research method used was a descriptive and evaluative quantitative approach, with data collected through questionnaires distributed to the pharmacists in charge of the pharmacies. The analysis was conducted using descriptive statistics to determine the level of compliance with pharmacy service standards. Based on the results, most pharmacies in Jepara Regency have implemented the seven aspects of clinical pharmacy services in accordance with the standards, as indicated by the high percentage of compliance in prescription assessment, dispensing, drug information services, and counseling, with several indicators reaching 100%. Home pharmacy care has been implemented by 51 pharmacies with a high level of compliance, while drug therapy monitoring and adverse drug reaction monitoring still show several indicators that have not been fully carried out by all pharmacies. Overall, the level of compliance of clinical pharmacy services in Jepara Regency falls into the good category and demonstrates that most pharmacies have met the standards set by the Ministry of Health Regulation No. 73 of 2016.